2004
DOI: 10.1007/s00213-004-1856-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum prolactin with severity of drug use and treatment outcome in cocaine dependence

Abstract: Although cocaine use seems to influence PRL levels, it does not appear that PRL is a predictor of treatment outcome in cocaine dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…As such, a tentative explanation for increased basal levels of prolactin in females may relate to a greater susceptibility to the neurotoxic effects of chronic cocaine abuse in women. However, further research is required to support this hypothesis, and while many studies have found a significant association between cocaine use and plasma prolactin levels, the implications of such findings as a predictor of treatment outcome have produced inconclusive results (Kranzler and Wallington 1992;Patkar et al 2002Patkar et al , 2004.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As such, a tentative explanation for increased basal levels of prolactin in females may relate to a greater susceptibility to the neurotoxic effects of chronic cocaine abuse in women. However, further research is required to support this hypothesis, and while many studies have found a significant association between cocaine use and plasma prolactin levels, the implications of such findings as a predictor of treatment outcome have produced inconclusive results (Kranzler and Wallington 1992;Patkar et al 2002Patkar et al , 2004.…”
Section: Discussionmentioning
confidence: 79%
“…However, in cocaine abusers, increases in basal prolactin levels could also be indicative of hyperprolactinemia, which has often been documented as an adverse effect of chronic cocaine abuse and/or abstinence (McDougle et al 1992;Teoh et al 1992). Findings from animal and human research indicate that such increases may be the result of perturbations in central dopaminergic function associated with chronic cocaine abuse (Patkar et al 2004) and may also be indicative of increased risk of relapse (Teoh et al 1990). In this study, there were no gender differences in cocaine-use profiles (see Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…Thus serum prolactin levels were suggested to reflect central dopamine activity. In a recent study with 141 AfricanAmerican cocaine dependent patients attending a treatment program, baseline prolactin levels were correlated with severity of dependence, measured using the ASI (56). Prolactin levels were not predictive of treatment retention or the number of drug free urines during treatment.…”
Section: Biological Markers Hormonesmentioning
confidence: 92%
“…These findings were replicated in another study with 141 African-American cocaine-dependent patients entering 12-week, outpatient treatment. Those with higher levels of impulsivity, measured with the Barratt Impulsiveness Scale, had worse treatment retention (56).…”
Section: Personality Traitsmentioning
confidence: 99%
“…More importantly from the standpoint of clinical prediction, high trait impulsiveness is associated with increased cocaine use quantity and long-term cocaine consumption (Moeller et al, 2001; Vonmoos et al, 2013), increased craving (Tziortis, Mahoney, Kalechstein, Newton, & De La Garza, 2011), fewer days of treatment attendance (Moeller et al, 2001; Patkar et al, 2004a, 2004b), greater withdrawal symptom severity (Moeller et al, 2001), and a greater number of depression symptoms (Vonmoos et al, 2013). …”
Section: Introductionmentioning
confidence: 99%